Pengaruh Faktor-Faktor Kepuasan Kerja Terhadap Kinerja Dosen PTS di Bogor - Pratomo, Anton Widio; Fitriyah, Idah; Gendalasari, Gen Gen (Program Vokasi dan LPPM IBI Kesatuan, 2024)
The purpose of this study was to test and analyze the effect of job satisfaction factors consisting of the work itself (X1), salary (X2), promotion opportunities (X3), supervision (X4) and co-workers (X5) on lecturer performance and the influence of variables X1, X2, X3, X4 & X5 simultaneously on lecturer performance. This study uses primary data through a survey of as many private university permanent lecturers (PTS) in Bogor. The collected data was processed and analyzed using SPSS software. From the results of this study indicate that; (1) work has a positive and significant effect on the performance of permanent lecturers at PTS in Bogor; (2) salary has no effect on the performance of permanent lecturers at PTS in Bogor; ; (3) promotion opportunities have no effect on the performance of permanent lecturers at PTS in Bogor; (4) supervisors have a positive and significant effect on the performance of permanent lecturers at PTS in Bogor; (5) colleagues have a positive and significant effect on the performance of permanent lecturers at PTS in Bogor; (6) variable X (factors of job satisfaction) as a whole is positive and significant to the performance of PTS lecturers in Bogor by 50.1% Keywords: work, supervision, colleagues, performance